2009
DOI: 10.4240/wjgs.v1.i1.56
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal symptomatic outcomes of laparoscopic and open gastrectomy

Abstract: AIM:To compare the laparoscopic and the open gastrectomy approaches for short term morbidity, length of hospital stay and also long term gastrointestinal symptoms. METHODS:Patients who have undergone gastrectomy had their medical records reviewed for demographic data, type of gastrectomy, short term morbidity, and length of hospital stay. Patients were contacted and asked to complete the Gastrointestinal Symptom Rating Scale (GSRS). The GSRS measures three domains of GI symptoms: Dyspepsia Syndrome (DS) for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…[ 10 11 12 ] Previous studies showed that laparoscopic procedures had less adverse gastrointestinal symptoms and resulted in faster gastrointestinal recovery than open surgery. [ 10 13 14 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 11 12 ] Previous studies showed that laparoscopic procedures had less adverse gastrointestinal symptoms and resulted in faster gastrointestinal recovery than open surgery. [ 10 13 14 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…More recently, several other authors have found similar benefits from laparoscopic gastrectomy compared with open surgery. [33][34][35][36][37][38][39][40] Our results have shown both low mortality (1.75%) and major morbidity (3.50%) rates for laparoscopic gastrectomy. This compares favourably with published literature regarding complications from open gastrectomy.…”
Section: Discussionmentioning
confidence: 93%
“…The smaller incision led to less tissue damage compared to conventional laparotomy and laparoscopic-assisted surgery 12) , this will reduce the obstruction caused by adhesion of the stomach or intestines and reduce abdominal pains. As compared to LAPPG, the small incisions required for TLPPG remained uniform in size between patients and were independent of patient factors, leading to a potential advantage for using the technique [13][14][15] . The score of the dyspepsia subscale was also lower than that of the PGSAS group.…”
Section: Discussionmentioning
confidence: 99%